Two pediatric cases of ameloblastic fibro-odontoma affecting the maxilla and mandible. Issue 1 (January 2023) - Takahashi, Kosuke; Suzuki, Yusuke; Eda, Takashi; Tajima, Mai; Yamazaki, Fumie; Takaku, Yuki; Ito, Ko; Kamei, Kazutoshi
Abstract: Ameloblastic fibro-odontoma (AFO) is an uncommon odontogenic tumor consisting of both odontogenic epithelium and odontogenic ectodermal mesenchymal tissues. Two pediatric cases of AFO are reported. Case 1: A 3-year-old girl was referred to our hospital for treatment of a radiolucent lesion in the right maxillary region. Radiographic examination showed a well-defined radiolucency containing a large number of calcifications. The clinical diagnosis was AFO, and surgical extraction was performed with the patient under general anesthesia. At the 48-month follow-up evaluation, there was no evidence of recurrence. Case 2: A 6-year-old girl was referred to our hospital for treatment of a radiolucent lesion in the left mandibular region. Radiographic examination showed a well-defined radiolucency containing a large number of calcifications. The clinical diagnosis was AFO, and surgical extraction was performed with the patient under general anesthesia. At the 12-month follow-up evaluation, there was no evidence of recurrence.